KEANEKARAGAMAN PLANKTON DI SUNGAI PELAWI DESA PELAWI UTARA KABUPATEN LANGKAT SUMATERA UTARA (Plankton Biodiversity in the Pelawi River North Pelawi Village Langkat District of North Sumatra) - Ester Nelya Tindaon; Yunasfi Djayus; Indra Lesmana (AQUACOASTMARINE, 2014)
Plankton is aquatic organism that flying and it is moves within the water current. Plankton is classified into phytoplankton (classified as plant) and zooplankton (classified as animal). The present of plankton in the water is determined by the physic and chemical condition of the water. Plankton has a limitation to tolerate the environment parameter, it’s diversity is different depend on physical and chemical conditions.The research has been done in Maret to April 2014. Samples were taken from three stations, and performed three times repeated checks in different periods of time by using Purposive Random Samplin. The result of research indicates thats there are 9 class of phytoplankton, they are : Bacillariophyceae, Chlorophyceae, Conjugatophyceae, Coscinodiscophyceae, Cyanophyceae, Dynophyceae, Eulenophyceae, Ulvophyceae, Zygnenophyceae and 8 class of zooplankton : Branchiopoda, Clitellata, Copepoda, Crustaceae, Gastropoda, Secernenta,Tubulinea, and Turbellaria. The highest total number of plankton is found in station I (206,00 ind/l) and the lowest total number of plankton is found on station 3 (33,33 ind/l). The highest diversity index value (H') for each station is found on station 1 (2,56) and the lowest on station 3 (2,16). The Pearson correlation of analysis indicates the brightness, DO, pH and nitrate have positive correlation to diversity of plankton while temperature, current, BOD5, and phosphate have negative correlation to diversity of plankton.Keywords : Water Quality, Plankton, Diversity, Sunggal River